A review of vocational education for special needs learners - Omar, Marlissa (Persatuan Pendidikan Teknik dan Vokasional Malaysia (PPTVM), 2019)
Malaysia has experienced a reform in its instructional system when the Minister of Education implemented inclusive education for kids with disabilities in all public school namely Zero Reject policy. Inclusive education implies more challenge is anticipated, particularly among educators or teachers who must cope with these special need's learners. For these special need's learners, however, opportunities for vocational education have long been implemented. The aim of this article is, therefore, to review publications linked to vocational education among learners with special needs. Review of the literature indicates an increase in publication rates in this region. Besides offering the education they deserve to these special needs learners, vocational education helps them explicitly to acquire work abilities that can be helpful for their future career.